Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Section 7.5 - Multiplying with More Than One Term and Rationalizing Denominators - Exercise Set - Page 550: 26


$2x-2\sqrt{2xy} + y$

Work Step by Step

RECALL: $(a-b)^2=a^2-2ab+b^2$ Use the formula above with $a=\sqrt{2x}$ and $b=\sqrt{y}$ to obtain: $=(\sqrt{2x})^2 - 2\sqrt{2x} \cdot \sqrt{y} + (\sqrt{y})^2$ Use the rules $(\sqrt{a})^2=a, a \ge 0$ and $\sqrt{a} \cdot \sqrt{b} = \sqrt{ab}, a, b, \ge 0$ to obtain: $\\=2x - 2\sqrt{2x(y)} + y \\=2x-2\sqrt{2xy} + y$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.